A Solution For Repairing Plastic Audio Nerves - Hadi, Parvane (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Did you hear about brain damages and people who lose their hearing because of it? or maybe you heard about plasticity nerve, but I have called them lazy nerves! when people talk to each other or watch TV and hear voices, lyrics,... it is because of neurons. Sounds have frequency and vibration, frequency is a rhythm, in physics it is measured as cycles per unit of time. If someone’s auditory nerve hurts they can’t hear well because voice frequencies reach to brain nerves for response by audio nerves. In this case, we can say their nerve is got plastic, or we can say their nerve is got lazy! People who have this issue use hearing-aid for helping them to hear a bit better, but they have a speech perception problem. We can improve their hearing by an attack on their auditory nerve with a wave with a low and high speed for force nerves to vibrate.